2020
DOI: 10.3389/fsufs.2020.583367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High and Low-Molecular-Weight Glutenins on the Processing Quality of a Set of Biofortified Common Wheat (Triticum aestivum L.) Lines

Abstract: Development of biofortified wheat lines has emerged as a sustainable solution to alleviate malnutrition. However, for these varieties to be successful, it is important that they meet the minimum quality criteria required to produce the local food products. In the present study, a set of 94 biofortified common wheat lines were analyzed for their grain micronutrients content (Fe and Zn) and for their processing quality and glutenin profile. Most of the analyzed lines exhibited a grain Zn concentration greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
6
6
1
Order By: Relevance
“…The significant positive correlations among GZnC, GFeC, and GPC indicate the possibility of simultaneous improvement of these traits. This finding is in line with earlier reports 44 , 49 52 . Additionally, many studies suggested a common genetic basis for these traits through GWAS and conventional QTL studies 50 , 51 , 55 , 56 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The significant positive correlations among GZnC, GFeC, and GPC indicate the possibility of simultaneous improvement of these traits. This finding is in line with earlier reports 44 , 49 52 . Additionally, many studies suggested a common genetic basis for these traits through GWAS and conventional QTL studies 50 , 51 , 55 , 56 .…”
Section: Discussionsupporting
confidence: 94%
“…The heritability estimates were higher (h 2 ≥ 0.60) for the studied traits, however, moderate heritability was found in some environments eg., > 0.40 and < 0.60 for GFeC in E1 and E4, GZnC and GPC in E4 (Table 1 ). The comparable heritability estimates were also reported in previous studies for these traits 29 , 32 , 49 – 53 .…”
Section: Discussionsupporting
confidence: 89%
“…Based on the best pleiotropic QTL combination, we have identified nine transgressive individuals from the RIL population that could be used in the breeding pipeline ( Table 6 ). The higher number of pleiotropic QTL for GZnC and GFeC obtained in the present study vis-à-vis previous studies is largely due to the higher correlation obtained between GZnC and GFeC as compared with previous studies ( Xu et al, 2012 ; Crespo-Herrera et al, 2017 ; Rathan et al, 2020 ). For example, Xu et al (2012) ; and Crespo-Herrera et al (2017) reported correlations between GZnC and GFeC ranging from 0.42 to 0.82 and 0.38–0.63, respectively, in different environments, whereas we obtained correlations ranging from 0.76 to 0.96 between the two traits in different years.…”
Section: Discussioncontrasting
confidence: 59%
“…The signi cant positive correlations among GZnC, GFeC and GPC indicate the possibility of simultaneous improvement of these traits (Table 3). This nding is in line with few earlier reports [40,[45][46][47]. Additionally, many studies suggested a common genetic basis of these traits through GWAS and QTL studies [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…Higher heritability indicates the greater contribution of genetic variance to the total variance and indicates the possibility of genetic improvement of traits through marker-assisted selection. Comparable heritability estimates were reported in some previous studies [29,32,45,46,47,48].…”
Section: Discussionsupporting
confidence: 84%